2020
DOI: 10.1186/s12886-020-01560-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and prognosis of Total Rhegmatogenous retinal detachment: a matched case-control study

Abstract: Background: Although many studies have reported clinical features, surgical outcomes of rhegmatogenous retinal detachment (RRD), studies focusing on total RRD are rare. In this study, we investigate the clinical characteristics, risk factors, and prognosis of total RRD. Methods: A retrospective chart review was performed on cases of 44 total RRD and an age-and sex-matched 88 partial RRD. Two groups were compared for clinical characteristics, risk factors, and prognosis. Results: The prevalence of total RRD in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Retinal detachment caused by dialysis and an inferior retinal break may progress slowly, and patients may not become aware of the symptoms at an early stage, which could be associated with the gradual progression of proliferation. A macular hole is reportedly observed frequently in total retinal detachment related to PVR [17]. Previous studies have shown that the baseline presence of PVR-C was related to ocular trauma [6,19] and a past history of uveitis [3,6,19] and inflammation is one of the major components of PVR formation [6,20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Retinal detachment caused by dialysis and an inferior retinal break may progress slowly, and patients may not become aware of the symptoms at an early stage, which could be associated with the gradual progression of proliferation. A macular hole is reportedly observed frequently in total retinal detachment related to PVR [17]. Previous studies have shown that the baseline presence of PVR-C was related to ocular trauma [6,19] and a past history of uveitis [3,6,19] and inflammation is one of the major components of PVR formation [6,20].…”
Section: Discussionmentioning
confidence: 99%
“…Primary analysis using the entire cohort revealed that the characteristics of retinal detachment were risk factors for the development of PVR-C: the area of retinal detachment was a risk factor for preoperative PVR-C with an OR of 5.42. In fact, it was reported that a wide area of retinal detachment was associated with PVR-C [17]. However, it is challenging to discern whether the wide area of retinal detachment was the cause or the result of PVR formation, because PVR formation can expand the detachment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, a considerable number of patients were classified as having complex RD, including those with macular hole (n = 18), complex cataract (n = 26), previous filtering glaucoma surgery (n = 13), chronic RD (n = 9), traumatic RD (n = 43), giant retinal tear (n = 21), total RD (n = 42) and vitreous haemorrhage (n = 82). Some of these factors have been shown to increase the risk of surgical failure, and this may explain our higher recurrence rates [ 18 , 19 , 20 , 21 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given that cataract surgery is currently the most common ophthalmic surgical procedure performed in our clinical setting [12], and that there is a boom of clear lens extraction in refractive surgery at younger ages, the incidence of PRD is expected to increase in the coming years. It should be noted that pseudophakic patients with RD achieve worse nal visual outcomes and that they experience a higher recurrence rate than phakic patients [13].…”
Section: Introductionmentioning
confidence: 98%